Multi-Node All-Optical Interconnect Network Routing for Data-Center Parallel Computers - Shuailong Yang; Liu Yang; Fengguang Luo; Biyu You; Yao Ni; Danhui Chen (IEEE Photonics Journal)
A multi-node all-optical interconnect network-routing architecture scheme and implementation technology are designed to improve high-speed and large-capacity data transmission in data centers. In the design of the optical interconnect routing electro-optic printed circuit board (EOPCB), the signal generated by the FPGA is directly modulated by the VCSEL arrays, and through the coupler into the parallel optical waveguide. The transmission link and optical switch are operated in optical domain. The designed optical waveguide comprises 12 waveguide arrays with the space of 250 μm. The all-optical interconnection routing system, which is based on the EOPCB high-speed chip multi-node waveguide, is designed, and a 4 × 4 EOPCB is fabricated. The performance of the waveguide and the entire optical interconnection network is tested. Based on 10 Gb/s VCSEL arrays, the optical interconnect network system can reach a bandwidth of 640 GHz for 4 × 4 networks. The best bit error rate for the switching system can reach 9.0 × 10–12 with no transmission error.